2018
DOI: 10.1016/j.clgc.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte Ratio, Platelet-to-lymphocyte Ratio, and C-reactive Protein as New and Simple Prognostic Factors in Patients With Metastatic Renal Cell Cancer Treated With Tyrosine Kinase Inhibitors: A Systemic Review and Meta-analysis

Abstract: Inflammation markers such as NLR, PLR, and CRP are predictors of clinical outcome and could provide additional information to individualize treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 47 publications
(86 reference statements)
4
54
1
Order By: Relevance
“…Similar results (worse OS in patients with high NLR) were described in prostate cancer [11]. In some studies, elevated NLR indicates a poorer prognosis for patients with RCC [12-14]. …”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar results (worse OS in patients with high NLR) were described in prostate cancer [11]. In some studies, elevated NLR indicates a poorer prognosis for patients with RCC [12-14]. …”
Section: Introductionsupporting
confidence: 66%
“…The result also indicated that an elevated PLR was significantly associated with poor OS in prostate cancer [22, 23]. In some studies, PLR has been demonstrated to be closely related to poor prognosis of patients with RCC [12, 24-26]. …”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, in various cancers [7], an elevated NLR is considered as a poor prognostic factor. NLR is an important factor that influence prognosis in ovarian, colorectal, breast, pancreatic, urothelial, renal cell cancers, and myeloma patients [8][9][10][11][12][13][14]. Recently, elevated NLR was reported to be correlated with poor prognosis in patients with gliomas in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the molecular‐targeted therapy era, the IMDC risk classification is a standard risk‐based stratification . Whereas the IMDC classification includes inflammatory markers, such as neutrophil and platelet count, several studies have suggested that systemic inflammation measured by NLR and CRP also plays a key role in prognosis in mRCC . Recently, the CAR, a novel inflammation‐based prognostic score, has shown outstanding prognostic value in several cancers .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Whereas the IMDC classification includes inflammatory markers, such as neutrophil and platelet count, several studies have suggested that systemic inflammation measured by NLR and CRP also plays a key role in prognosis in mRCC. [14][15][16] Recently, the CAR, a novel inflammation-based prognostic score, has shown outstanding prognostic value in several cancers. [17][18][19] However, only a few studies investigated the impact of CAR on prognosis in patients with mRCC, and no study compared the effect of CAR with the mGPS on prognosis in mRCC.…”
Section: Introductionmentioning
confidence: 99%